Akad Ijarah Dalam Pembiayaan Pegadaian Syariah: Analisis Terhadap Fatwa Dsn-Mui No. 25/DSN-MUI/III/2002 - Muhamad Annas; Nurul Inayah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study examines the implementation of ijarah contracts in sharia pawn financing by referring to the provisions of DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 on rahn. Normatively, the fatwa stipulates that ijarah fees for maintenance and storage of collateral may not be determined based on the amount of financing provided. However, in practice, sharia pawn institutions often apply ijarah tariffs that vary according to the size of the loan, raising questions regarding their compliance with sharia principles. This research employs a normative juridical method with statutory and conceptual approaches, using DSN-MUI fatwas and relevant legal literature as primary and secondary legal materials. The findings indicate that the determination of ijarah fees in sharia pawn financing is still linked to the amount of financing disbursed, rather than to the actual cost of storage and maintenance of the collateral. Consequently, such practices are not fully aligned with the normative provisions of sharia law as regulated by DSN-MUI. This study contributes to the development of sharia economic law by providing a normative evaluation of ijarah implementation in contemporary sharia pawn practices and offering a basis for regulatory and institutional improvements.